MASJID LAMA BATU 6, BATU 6 JALAN GOMBAK, 53100 KUALA LUMPUR, SELANGOR MALAYSIA - Siddiqua, Rahnoma; Wan Mohd Kamal, Wan Nur Natasha; Adlan, Nur Farahadlin; Muhammad Hizer, Mohammad Arieff; Laila Satria, Amirul Amran; Mohlis, Muhammad Arif Azfar; Asfarina, Naura; Roslan, Kamal Syarafi; Wan Zamharir, Wan Nur Amalya; Norhan, Amirul Hafiz; Mohd Nasir, Fahirah Izzati; Zahari, Muhammad Arif Haikal; et al. (Department of Architecture, Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2021)
The study of Masjid Lama Batu 6 in Gombak takes us back to the early Minang establishments in the area, along with the importance of the Masjid in a community and how it is designed to function as a place of worship, gathering and religious or educational activities. Although built in 1931, talk of an older masjid along the Sungai Gombak still remains to this day. The Masjid, however, is now adjacent to the main road Jalan Gombak and has modern additions to it and plans for future renovations continue. However, many elements, such as the roof structure and the timber column ‘tiang’ or soko guru, have still been kept from the original masjid. The study of Masjid Lama Batu 6 comprises the building’s and its physical site’s evolution throughout history, the surrounding culture of the people as well as its neighbourhood context. The Masjid, to this day, essentially functions as a core part of the community, holding religious as well as social requirements of Muslims, with the space for prayer as well as an adjoining hall to multi-function as an extended prayer space or to provide an educational and/or event space. The first part of the report conveys the analytical studies of Masjid Lama Batu 6, which include: history, chronology, architectural influences, the site context of the masjid, the culture and social aspects along with the migration of the first society with the new society of Batu 6. The second part of the report is a compilation of measured drawings of Masjid Lama Batu 6 Gombak. The report further evaluates the structure of the masjid, how the role of culture and religion in shaping the architecture of masjids in the region and how other factors such as climate, geography and technology can affect a building design. Ultimately, the studies are made to benefit the generations to come on the local masjid and their unique heritage.